Synthesis and Electrical Properties of Well-Ordered Layered α-MoO3 Nanosheets - Naoue, R.; Dhaouadi, H.; Touati, F.; Gharbi, N. (Nano-Micro Letters, 2011)
α-MoO3 ordered nanosheets have been synthesized under hydrothermal conditions using commercial MoO3 and hydroquinone as structuring agent. X-ray diffraction (XRD), scanning electron microscope (SEM) and transmission electron microscopy (TEM) were used to analyse the obtained material. The conductivity mechanism of the Molybdenum ordered nanosheets has been investigated using combined complex impedance and modulus formalism. The temperature dependence of the conductivity, which was between 473 and 573 K, is very close to the Arrhenius’ law, with an activation energy of 0.76 eV. However, the conductivity of the material increases with temperature. It shows a typical negative temperature coefficient resistance (NTCR) similar to that of a semiconductor. The dielectric properties of the MoO3 compound have been studied in the temperature range of 473–573 K as well as the frequency range of 10 Hz to 13 MHz. The ac-conductivity for high frequency σac (ω) obeys the universal power law.